Physical functioning and health-related quality of life after COVID-19: a long-term perspective case series. Issue 1 (26th December 2022) - Ferrarello, Francesco; Iacopino, Carmela; Pierinelli, Catia; Paci, Matteo
Abstract : The purpose of our study was to monitor the long-term changes in physical functioning and health-related quality of life in individuals who received outpatient rehabilitation after COVID-19. Individuals referred to outpatient rehabilitation for post-COVID-19 physical therapy were assessed before the treatment, at the end of the treatment, and 2 and 6 months after the end of the treatment. The physical functioning was assessed by Barthel Index, Timed Up and Go test, Short Physical Performance Battery test (SPPB), Patient-Specific Functioning Scale (PSFS), and EuroQOL 5D-3L. Friedman's test was utilized to assess changes in the assessments. The proportions of individuals showing variation in performance equal to or greater than the absolute minimal detectable change (MDC) value of the SPPB and PSFS were calculated. Forty-four cases were monitored for 7.3–15.6 months. At baseline, they showed substantial independence in activities of daily living, moderate mobility limitations, and below-average health-related quality of life. Their status significantly improved over time (Friedman's test P = 0.002 to <0.001); post hoc analysis confirmed the improvement of mobility and health-related quality of life at 6-month follow-up relative to the baseline. After accounting for MDC values, 55% meaningfully improved on SPPB and 45% on PSFS, although some worsened (11 and 5%, respectively) and the remaining showed no meaningful change. Despite good independence in activities of daily living and perceived health, individuals surviving the COVID-19 may not have fully recovered their premorbid functioning status seven to 15 months after the infection.